Purple sweet potato (Ipomoea batatas) flour in bread making. - Armada, John Vincent E. (2014.)
Purple sweet potato (PSP) flour as substitute for wheat flour in bread. Anthocyanin content and radical scavenging activity (RSA) was determined in unprocessed PSP and PSP flour. The anthocyanin content of the unprocessed PSP were 21.46 mg L-1, 25.89 mg L-1 and 27.73 mg L-1. The anthocyanin content of the PSP flour were: 32.56 mg L-1, 33.06 mg L-1, 34.99 mg L-1, and 36.57 mg L-. The RSA of the unprocessed PSP were 72.5163%, 73.04%, 73.44%, and 74.11% respectively. The RSA of the PSP flour were 73.25%, 73.35%, 73.35%, 73.93% and 73.98% respectively. A significant increase (P<0.05) in anthocyanin content between unprocessed PSP and PSP flour at was observed. The increase may be attributed to the transformation of the other forms of anthocyanin into the measured forms. These forms may be cyanidin and peonidin derivatives acylated with one or two cinnamic acid that were found in PSP by Xu (2011). However, no significant difference (P>0.05) in RSA between unprocessed and PSP flour was observed. Therefore, the antioxidant activity of PSP was not affected by processing. In the unprocessed PSP, anthocyanin content and RSA were higly correlated (0.758). In contrast, no correlation was observed between anthocyanin and RSA in PSP flour. Bread was processed at varying wheat to PSP flour ratios: 75:25 (Formulation 1), 50:50 (Formulation 2), and 25:75 (Formulation3). Formulation 1 was considered as the most preferred formulation. Its proximate composition (%): moisture content, 29.5; crude protein, 8.16; crude fat, 2.51; ash, 2.60; crude fiber, 1.59 and carbohydrates, 55.7. It is typically a carbohydrate food. Formulation 1 was rated ?like slightly? similarly with Formulation 2, while Formulation 3 was rated ?dislike slightly?. Based on general acceptability, increase in the level of PSP in bread has reduced its acceptability. PSP flour can be used as a substitute for wheat flour in bread making at less than 25% level of substitution.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Sweet potato; Ipomoea batatas; Flour; Bread; Bread making